2010
DOI: 10.1017/s0008413100001353
|View full text |Cite
|
Sign up to set email alerts
|

Lexical frequency as a scalar variable in explaining variation

Abstract: This study examines the relationship between lexical frequency and s-lenition in Barranquillero Spanish, looking at lexical frequency as a scalar variable. A quantitative analysis of /s/ in words of different lexical frequencies, in which productions from a reading task were submitted to auditory acoustical analysis, reveals that the single most important factor in s-lenition is lexical frequency. Speakers tend towards a full articulation of /s/ in low-frequency words, while weakening it in high-frequency word… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…In the usage-based model of phonology and in exemplar theory (Bybee, 2001, 2006), the claim is made that high-frequency lexical items or phrases generally undergo regular sound change before low-frequency words. In the case of Spanish /s/ lenition, a number of recent studies (Bybee, 2002; E. K. Brown, 2009a, 2009b; E. L. Brown, 2005; E. L. Brown & Torres Cacoullos, 2002, 2003; File-Muriel, 2009, 2010; Minnick Fox, 2006) have demonstrated that /s/ is more likely to be lenited in more frequent words.…”
Section: Previous Studies and Their Methodologiesmentioning
confidence: 99%
“…In the usage-based model of phonology and in exemplar theory (Bybee, 2001, 2006), the claim is made that high-frequency lexical items or phrases generally undergo regular sound change before low-frequency words. In the case of Spanish /s/ lenition, a number of recent studies (Bybee, 2002; E. K. Brown, 2009a, 2009b; E. L. Brown, 2005; E. L. Brown & Torres Cacoullos, 2002, 2003; File-Muriel, 2009, 2010; Minnick Fox, 2006) have demonstrated that /s/ is more likely to be lenited in more frequent words.…”
Section: Previous Studies and Their Methodologiesmentioning
confidence: 99%
“…Apart from the inherent problem of deciding on the appropriate source for the measurement of frequency, the restriction to nominal factor groups forces us to make arbitrary decisions about categorizing frequency (Pierrehumbert, 2006:519). Thus, if frequency has the consistent, monotonic effect predicted by a usage-based account, this effect may be masked by dividing the continuum of frequency into discrete categories (File-Muriel, 2010:19). However, if frequency effects simply reflect the skewed distribution of morphological categories across frequency categories, GoldVarb provides no way of taking this skewing into account.…”
Section: (T/d)-deletion In Toronto Englishmentioning
confidence: 99%
“…For our second research question on the linguistic/social predictors of SCPS /s/, the findings of our logistic regressions (based on the discrete coding) suggest that following stop consonant is the most robust predictor of /s/ realization: /st/ favors alveolar fricatives, /sk/ favors velar fricatives, and /sp/ favors glottal fricatives/deletions. This is not the first study to indicate a strong effect of the following phonological context on Spanish coda /s/ (see Méndez Dosuna 1985, Brown 2009, File-Muriel 2010. In a study of /s/ across post-consonantal contexts, Brown (2009) shows that following /t/ most commonly favors /s/ retention when compared to all other following consonants (a finding supporting the claim that Spanish adopts regressive assimilatory processes to a greater extent than progressive assimilatory processes; Schwegler, Kempff & Ameal-Guerra 2010: 243-246;File-Muriel & Brown 2011: 239).…”
Section: Answering the Research Questionsmentioning
confidence: 80%